First-in-child use of the oral soluble guanylate cyclase stimulator riociguat in pulmonary arterial hypertension. (December 2017) - Spreemann, Till; Bertram, Harald; Happel, Christoph M.; Kozlik-Feldmann, Rainer; Hansmann, Georg
Riociguat has been approved for use in adults with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension. No clinical data on its therapeutic use in children with PAH are currently available. We report the case of a now four-year-old boy who initially presented at the age of 10 months with suprasystemic pulmonary hypertension (PH) and right ventricular (RV) failure, vomiting, peripheral cyanosis, and failure to thrive. Cardiac catheterization revealed severe PAH. At radiologic suspicion of interstitial lung disease, repeated CT scan and an open lung biopsy were performed but could not clarify the entity of PAH. Given the demonstrated vasoreactivity, the boy was started on the calcium channel blocker amlodipine, in combination with the endothelin-1 receptor antagonist bosentan. Two years later, based on persistently systemic PAH with lost vasoreactivity, PAH therapy was changed to bosentan and phosphodiesterase-5 inhibitor sildenafil. No significant improvement on the aforementioned therapy was seen, so that the patient was referred to our institution. Invasive hemodynamic evaluation showed suprasystemic PAH and marked acute vasoreactivity (PAP 127/103/83 mmHg, PVRi 23.48 WU·m 2 and PVR/SVR ratio 1.59 at baseline vs. PVRi 5.89 WU·m 2 and PVR/SVR ratio 0.93 under O2 /NO). Subsequently, we switched the patient from sildenafil to riociguat. After six months on bosentan/riociguat, the patient showed a marked decrease in PVR/SVR and transpulmonary pressure gradients, in RV hypertrophy, PA acceleration time, and left ventricular-eccentricity index. Clinically, the patient improved in pediatric functional class from 2/3 to 1. In conclusion, off-label use of oral riociguat may be considered in selected children with severe PAH.